Members of the Genera Paenibacillus and Rhodococcus Harbor Genes Homologous to Enterococcal Glycopeptide Resistance Genes vanA and vanB - Guardabassi, L. (American Society for Microbiology, 2004)
Genes homologous to enterococcal glycopeptide resistance genes vanA and vanB were found in glycopeptide-resistant Paenibacillus and Rhodococcus strains from soil. The putative d-Ala:d-Lac ligase genes in Paenibacillus thiaminolyticus PT-2B1 and Paenibacillus apiarius PA-B2B were closely related to vanA (92 and 87%) and flanked by genes homologous to vanH and vanX in vanA operons.